The Effect of IAA, BAP, and Coconut Water on Tomato (Solanum lycopersicum L.) Organogenesis - Alba Wijaya Maharani; Restiani, Ratih; Aniek Prasetyaningsih (Jurnal Biodjati, 2025)
Tomato (Solanum lycopersicum L.) is a widely cultivated horticultural crop valued for its phytochemical and nutritional content. The increasing demand for high-quality seedlings has promoted the use of in vitro propagation, which offers greater efficiency in labor and land use, uniform seedling production, and independence from climate compared to conventional methods. This study aimed to investigate the effect of different concentrations of plant growth regulators (PGRs) and coconut water as an alternative or supplement on the organogenesis of tomato hypocotyl explants. Tomato hypocotyl explants were cultured on Murashige and Skoog (MS) medium supplemented with different concentrations of BAP (0.5, 1.0, and 1.5 ppm), IAA (0.1, 0.3, and 0.5 ppm), and coconut water (10%, 20%, and 30%). The experiment was arranged in a Completely Randomized Design (CRD) with four replications, consisting of a control, single-factor treatments, and combination treatments of BAP, IAA, and coconut water. Observations included the percentage and intensity of root, shoot, and callus formation, as well as shoot height. Data were analyzed using the non-parametric Kruskal–Wallis test, followed by Dunn’s test. The results showed that roots, shoots, and callus successfully developed in treatments supplemented with 6-benzylaminopurine (BAP), indole-3-acetic acid (IAA), and coconut water. The highest shoot growth, with a percentage of 87.7% and an average height of 5.75 cm, was observed in treatment K20, while the highest callus formation occurred in treatment K30. The best shoot and callus intensities were resulted in media with coconut water alone at concentrations of 10%, 20%, and 30%, whereas the highest root intensity was obtained in the BAP+IAA treatment without coconut water. The results indicate that coconut water is effective in supporting organogenesis, both directly through the formation of shoots and roots, and indirectly through callus formation that can subsequently develop into shoots and roots.